The Challenges in Undertaking English Speech Training Program at an Islamic Boarding School : A Study of Studentsâ€™ Perspectives - Abubakar, Bahrun; Atmowardoyo, Haryanto; Korompot, Chairil Anwar (ELT Worldwide: Journal of English Language Teaching, 2017)
The objectives of this research were to find out (1)the studentsâ€™ perspective about the English Speech Training through the Muhadharah Program at IMMIM Putera Islamic Boarding School; (2) the most significant problems that challenge the students in undertaking English Speech Training through the Muhadharah Program; (3) the actions that the students already tookÂ  in attempt to deal with the problems they had in undertaking the English Speech Training through the Muhadharah Program.This research employed descriptive qualitative research design. It applied purposive sampling technique. The participants of this research were two students, they are grade 2: 1 student and grade 6: 1 student. The data were collected by using interview and observation. The interview was used to gather the data about the studentsâ€™ perspectives on the English Speech Training through the Muhadharah Program at IMMIM Putera Islamic Boarding School, the challenges they faced and the solutions they took dealing with the English Speech Training through the Muhadharah Program. The result of research showed that (1) the perspectives of the students on the Muhadharah program in IMMIM Putera Islamic Boarding School are quite positive; (2) the most significant problems that challenge the students in undertaking the program are mostly related to the linguistic factors; peersâ€™ generated anxiety; monotonous design of the program; and speech by rote; (3) the solutive action taken by the students to tackle the problems in undertaking the Muhadharah program; preparing the speech materials and speech techniques. This is done in two ways: consulting to supervising teachers (done by junior students); preparing everything independently (done by senior students). The implications of this research are; (1) promoting a term to address a new speaking feature called â€œSpeech by Roteâ€; (2) pesantren should recruit supervising teachers with good English command; (3) pesantren should vary the design of the program.